Electro-optical memory of a nematic liquid crystal doped by multi-walled carbon nanotubes - Dolgov, L.; Yaroshchuk, O.; Tomylko, S.; Lebovka, N. (Condensed Matter Physics, 2012)
A pronounced irreversible electro-optical response (memory effect) has been recently observed for nematic liquid crystal (LC) EBBA doped by multi-walled carbon nanotubes (MWCNTs) near the percolation threshold of the MWCNTs (0.02÷0.05 wt. %). It is caused by irreversible homeotropic-to-planar reorientation of LC in an electric field. This feature is explained by electro-hydrodynamically stimulated dispergation of MWCNTs in LC and by the formation of a percolation MWCNT network which acts as a spatially distributed surface stabilizing the planar state of the LC. This mechanism is confirmed by the absence of memory in the EBBA/MWCNT composites, whose original structure is fixed by a polymer. The observed effect suggests new operation modes for the memory type and bistable LC devices, as well as a method for in situ dispergation of carbon nanotubes in LC cells. В нематичному рiдкому кристалi (РК) ЕББА, допованому багатошаровими вуглецевими нанотрубками (БШВНТ), поблизу перколяцiйної концентрацiї БШВНТ (0.02 ÷ 0.05 ваг. %) нещодавно спостережено виразний необоротний електрооптичний вiдгук (ефект пам’ятi). Цей ефект викликаний необоротною переорiєнтацiєю РК в електричному полi з гомеотропного у планарний стан. Ця особливiсть пояснюється електрогiдродинамiчно стимульованою диспергацiєю БШВНТ в РК i формуванням перколяцiйної сiтки БШВНТ, яка дiє як просторово розподiлена поверхня, що стабiлiзує планарний стан РК. Цей механiзм пiдтверджується вiдсутнiстю пам’ятi в композитах ЕББА/БШВНТ, у яких початкова структура зафiксована полiмером. Цей ефект може бути корисним для розробки нових типiв запам’ятовуючих та бiстабiльних РК пристроїв, а також для пiдсилення диспергацiї БШВНТ безпосередньо в РК комiрках.